Obesity and Food Away from Home : What Drives the Socioeconomic Gradient in Excess Body Weight ? - Strupat, Christoph; Farfan, Gabriela; Moritz, Laura; Negre, Mario; Vakis, Renos (World Bank, Washington, DC, 2019)
Rising obesity rates are one of the most challenging public health issues in many emerging economies. The extent to which the nutritional composition of food consumed away from home is behind this rise, and the links with socioeconomic status, is not yet well understood. This paper explores this question by combining a representative restaurant survey that includes detailed information on the nutritional composition of the most widely consumed meals in Metropolitan Lima and a representative household survey with anthropometric measures of adult women. The findings indicate that the nutritional quality in restaurants located in the food environment of the households is significantly associated with higher rates of obesity and overweight. Up to 15 percent of the socioeconomic gradient in obesity is attributable to restaurant food quality, with sodium being the main driver. This highlights the importance of considering the food environment to inform public health policies, particularly for the poor.